Pengaruh Tipe Kepribadian dan Perbedaan Jenis Kelamin Terhadap Hasil Belajar Mata Kuliah Micro Konseling pada Mahasiswa Jurusan Dakwah STAIn Purwokerto - Nur Azizah (STAI ALHIKMAH Jakarta, 2017)
The purpose of this research is to find out the influence of personality type and gender differences on the students’ results of micro-counseling subject in department of Da’wah STAIN Purwokerto. The populations of the research are students majoring in Dakwah. The subjects are 70 students, which consist of 30 male and 40 female with extrovertand introvertpersonality type. The data are collected by using questionnaire of Personality. The validity and reliabilityoftheinstrumentsareassessedbyusingPearson’sProductMoment correlation and Cronbach’s Alpha coefficient. The data are analyzed using 2-Ways ANOVA technique by means of Microsoft office excel 2007. The result of this study shows that (1) there is a very significant interaction effect between factor A (personality types) and factor B (Sex Differences), or the influence of personality type on the results of study Micro counseling subjects depends on Gender Differences (Fhit = 49.074>Ftabel = 4.062); (2) there are differences in average learning outcomes of courses of group micro -counseling between male and female (Fhit 6.292>Ftabel 4.062); and(3) therearedifferencesinaveragelearning outcomes Micro counseling courses from groups that have a personality type Extroverts and Introverts. (Fhit 4.886 > Ftabel 4.062). Keywords : personality type, gender differences, learning result of micro-counseling. The purpose of this research is to find out the influence of personality type and gender differences on the students’ results of micro-counseling subject in department of Da’wah STAIN Purwokerto. The populations of the research are students majoring in Dakwah. The subjects are 70 students, which consist of 30 male and 40 female with extrovertand introvertpersonality type. The data are collected by using questionnaire of Personality. The validity and reliabilityoftheinstrumentsareassessedbyusingPearson’sProductMoment correlation and Cronbach’s Alpha coefficient. The data are analyzed using 2-Ways ANOVA technique by means of Microsoft office excel 2007. The result of this study shows that (1) there is a very significant interaction effect between factor A (personality types) and factor B (Sex Differences), or the influence of personality type on the results of study Micro counseling subjects depends on Gender Differences (Fhit = 49.074>Ftabel = 4.062); (2) there are differences in average learning outcomes of courses of group micro -counseling between male and female (Fhit 6.292>Ftabel 4.062); and(3) therearedifferencesinaveragelearning outcomes Micro counseling courses from groups that have a personality type Extroverts and Introverts. (Fhit 4.886 > Ftabel 4.062). Keywords : personality type, gender differences, learning result of micro-counseling.